Evaluation of the period of filling and intestinal evacuation of Brachionus calyciflorus fed on Chlorella sp. (Orinoquia, 2019)
In order to determine the viability of the freshwater rotifer Brachionus calyciflorus used as alive food in the phase of larviculture of ictic species,there was evaluated the chronological period of filling and intestinal evacuation, by means of the supply with different concentrations of microalgae Chlorella sp. in condensed condition. The treatments were, T1: 1.2 × 106 cells / mL, T2: 5.2 × 106 cells / mL, T3: 10.4 × 106 cells / mL and T4: 15.4 × 106 cells / mL, all of them with a density of 40 for each treatment. Analysis of image was realized, and it was applied a test of variance ANOVA and Tukey›s multiple test to the results where significant differences between the treatments were established (P≤0.05); the variables analyzed were: volume of body, bowel volume, intestinal volume expressed in percentage and intestinal transit time. For morphometric Univeranalysis, the volume rank of the body was of 0,7×106 μm3 to 2,6 ×106 μm3. The minimum filling and evacuation time were 60 minutes. The intestinal percentages in their maximum repletion for each treatment were T1: 5.55%, T2: 8.62% T3: 10.53% and T4: 8.08%, consequently, the suitable time to supply the rotifer B. Calyciflorus as alive food in larviculture it is of 105 - 225 minutes, after initiated the ingestion of the microalgae.
Keywords: alive food; microalgae; rotifer; intestinal volume